Knowledge As a Factor to Improve Competitiveness for a Firm in Rural Norway - Knut Ingar Westeren (European Regional Science Association (ERSA), 2006)
Aker Verdal produces steel jackets for the offshore industry and is situated in Trøndelag in peripheral Norway. The firm has about 600 employees and a yearly production value of about 200 mill. . The main competitors are in the southern part of Europe, for example Dragados in Spain. The wage level at Dragados is about 50% lower than at Aker Verdal, but Aker has won several contracts in the later years. One reason for this is that Aker has a knowledge component that contributes to the compensation for higher wage costs. The firm wants to analyze how it acquires and develops knowledge capital by looking at: · Identification: What are the central knowledge processes that take place · Measurement: What kind of indicators can be used · Management: How is management of knowledge integrated in the general management of the firm In this paper we will look at a case study and see how that can be understood in a theoretical framework. We will also analyze the advantages and disadvantages of peripheral location and its influence on knowledge creation and development.
Keywords: 330